A bismaleimide resin containing polybutadiene chain segments and its preparation method and application
By introducing polybutadiene segments into bismaleimide resins, a high saturation double bond structure is formed, which solves the problems of high cost, difficult processing, poor recyclability and market competition pressure of BMI resins, and achieves high performance and good processability resin materials.
Patent Information
- Application Number
- CN202411855701.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing bismaleimide (BMI) resins have challenges in terms of high cost, difficult processing, poor recyclability and market competition pressure.
A bismaleimide resin containing polybutadiene segments is developed, which is liquid at room temperature and is prepared by specific compound reactions and processes to form a double bond structure with high saturation, improving its stability and processability at high temperatures.
It achieves excellent stability and chemical resistance at high temperatures, and has good processability at room temperature, which reduces production costs, improves recyclability, and enhances market competitiveness.
Smart Images

Figure CN119320468B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a bismaleimide resin containing a polybutadiene chain segment and a preparation method and application thereof. Background Art
[0002] Bismaleimide (BMI) resin is a type of high-performance thermosetting resin material with high thermal stability, excellent mechanical properties, low moisture absorption rate and low expansion coefficient, as well as excellent electrical properties. It is widely used in aerospace, automotive, electronics and other fields. In particular, the high heat resistance of BMI resin enables it to perform well in extreme environments and maintain excellent mechanical properties under high temperature conditions. Therefore, it is widely used in the aerospace field to manufacture high-temperature structural parts, such as engine components and spacecraft thermal protection materials. In addition, BMI resin also has excellent electrical properties, which makes it used in the electronics industry to manufacture high-performance electronic components and circuit boards. This resin material can be prepared into parts of various shapes and sizes through a variety of processes such as hot pressing and hot injection molding. Overall, BMI resin occupies an important position in the high-demand engineering field with its excellent comprehensive performance, providing reliable material solutions for various complex applications.
[0003] Although BMI resin has excellent performance in many fields, it still faces some challenges and problems. Here are some of the main problems with BMI resin at present: 1. High cost: The production cost of BMI resin is relatively high, which makes it not the most economical and affordable choice in some applications. This may be a constraint for some large-scale production and cost-sensitive industries. 2. Difficult processing: BMI resin has a high melting point due to the presence of a large number of imide rigid groups in its molecular structure, and requires high-temperature melting or the addition of a large amount of volatile solvents to assist processing. This makes the processing technology complicated and limits its widespread adoption in some applications. Although BMI resin has excellent mechanical properties at high temperatures, it may exhibit high brittleness at room temperature, which may be a problem in some applications, especially for scenarios requiring high toughness. 3. Recyclability: BMI resin is usually cured at high temperatures, which may affect its recyclability. This may be a consideration in some fields with high requirements for sustainability and circular economy. 4. Market competition: With the continuous emergence of new high-performance resins, BMI resin faces competitive pressure in the market. Therefore, continuous improvement and innovation are needed to remain competitive. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a bismaleimide resin containing a polybutadiene segment and a preparation method and application thereof. The bismaleimide resin of the present invention is liquid at room temperature, giving it better processability, and is a high-performance BMI resin material.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a bismaleimide resin having a structure as shown in Formula 1 below:
[0007]
[0008] Formula 1
[0009] Wherein R1 is selected from C1-C5 alkylene, n is an integer of 20-40 (e.g., 20, 23, 25, 28, 30, 33, 35, 38, 40, etc.), 0<a<1, 0<b<1, 0<c<1, and a+b+c=1.
[0010] In the present invention, a can be 0.1, 0.2, 0.3, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 0.95, etc., b can be 0.1, 0.2, 0.3, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 0.95, etc., c can be 0.1, 0.2, 0.3, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 0.95, etc., and a+b+c=1 is satisfied.
[0011] In the present invention, in the bismaleimide resin having the structure shown, two maleimide groups are distributed at both ends, and the structure contains double bonds, and its saturation is relatively high, which gives the resin excellent stability and chemical resistance at high temperatures. During the hardening process, the BMI resin forms a three-dimensional network structure through thermal cross-linking, which enhances its mechanical properties and high temperature resistance. This cross-linked structure helps to improve the thermoplasticity of the resin.
[0012] In the present invention, R1 is selected from -CH2-, -CH2-CH2- or -CH2-CH2-CH2-CH2-CH2-
[0013] Preferably, the bismaleimide resin is selected from any one of the following resins:
[0014] ;
[0015] .
[0016] On the other hand, the present invention provides a method for preparing the bismaleimide resin as described above, the preparation method comprising the following steps:
[0017] (2) The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows:
[0018] ;
[0019] wherein R1, n, a, b and c are the same as defined above.
[0020] Preferably, the molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:1, for example 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.
[0021] Preferably, the reaction is carried out in the presence of a dehydrating agent.
[0022] Preferably, the molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.7, 1:1.8, 1:1.9 or 1:2.
[0023] Preferably, the dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide (DCC), diisopropylcarbodiimide (DIC) or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI).
[0024] Preferably, the reaction is carried out in the presence of a catalyst.
[0025] Preferably, the catalyst is selected from at least one of 4-dimethylaminopyridine (DMAP), 4-pyrrolidinylpyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate.
[0026] Preferably, the molar ratio of the catalyst to the compound represented by formula B is 1:10-1:15, for example 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.
[0027] Preferably, the reaction is carried out at room temperature (i.e. 15-35°C, such as 15°C, 18°C, 20°C, 25°C, 30°C or 35°C) for 12-24 h, such as 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h.
[0028] In another aspect, the present invention provides use of the bismaleimide resin described above in the preparation of a thermosetting material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The bismaleimide resin of the invention has excellent stability and chemical resistance at high temperatures, good mechanical properties and high temperature resistance, is liquid at room temperature, has good processability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the thermogravimetric analysis result of BMI-PPG400, BMI-PPG1000 and BMI-R45V. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0033] Preparation Example 1
[0034] Synthesis of Bismaleimide Resin
[0035]
[0036] Dissolve maleimide propionic acid (253.5 g, 1.5 mol) in 2500 mL of dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309 g, 1.5 mol) in 300 mL of dichloromethane, slowly drop the DCC solution into the maleimide propionic acid solution under stirring, and continue stirring and reacting for 10 min after all the additions are completed. Then add (hydroxy-terminated polybutadiene, Total) Polybd R45V (1400 g, 0.5 mol) into the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1 g, 0.05 mol), and stop the reaction after 8 h. The insoluble matter was filtered off, and the filtrate was taken into a separatory funnel and extracted with water. The organic layers were combined and dried over anhydrous Na2SO4. The filtrate was spin-dried to obtain a red viscous liquid. After standing and cooling, a small amount of solid precipitated, which was filtered again to obtain the final product BMI-R45V.
[0037] The product was characterized by hydrogen NMR spectrum, and its NMR data are as follows: 1H NMR (500 MHz, Chloroform-d)δ 6.97 (dt, J = 14.5, 0.9 Hz, 1H), 6.64 (s, 4H), 5.83 – 5.56 (m, 4H), 5.05(tdd, J = 15.9, 2.2, 1.0 Hz, 2H), 4.59 (dp, J = 4.2, 1.0 Hz, 2H), 4.27 – 3.85 (m, 4H), 2.96 – 2.64 (m, 4H), 2.27 (ddddd, J = 9.2, 8.2, 6.3, 2.0, 1.1 Hz,1H), 2.17 – 1.87 (m, 4H), 1.68 – 1.40 (m, 2H).
[0038] Preparation Example 2
[0039] The preparation method of the compound comprises the following steps:
[0040] Dissolve maleimidocaproic acid (315 g, 1.5 mol) in 2500 mL of dichloromethane, then dissolve dicyclohexylcarbodiimide (DCC) powder (309 g, 1.5 mol) in 300 mL of dichloromethane. Slowly drop the DCC solution into the maleimidocaproic acid solution under stirring. After all the additions are completed, continue stirring and reacting for 10 min. Then add (hydroxy-terminated polybutadiene, Total) Polybd R45V (1400 g, 0.5 mol) into the system; finally, slowly add 4-dimethylaminopyridine (DMAP) powder (6.1 g, 0.05 mol) and stop the reaction after 8 h. Filter and remove the insoluble matter, take the filtrate and extract it with water in a separatory funnel, combine the organic layers, dry them over anhydrous Na2SO4, spin dry the filtrate to obtain a red viscous liquid, and a small amount of solid precipitates after standing and cooling. Filter again to obtain the final product.
[0041] The product was characterized by hydrogen NMR spectrum, and its NMR data are as follows: 1H NMR (500 MHz, deuterated chloroform) δ6.95 (dt, J = 14.5, 0.9 Hz, 1H), 6.71 (s, 4H), 5.84 – 5.56 (m, 4H), 5.05(tdd, J = 16.0, 2.2, 1.0 Hz, 2H), 4.59 (ddt, J = 4.3, 1.8, 0.9 Hz, 2H), 3.72– 3.57 (m, 4H), 2.39 – 2.30 (m, 4H), 2.30 – 2.22 (m, 1H), 2.09 – 1.99 (m,4H), 1.73 – 1.66 (m, 4H), 1.64 – 1.47 (m, 6H), 1.44 – 1.35 (m, 4H).
[0042] Comparative Example 1
[0043] BMI-PPG1000 disclosed in CN117844435A was used as comparative compound 1.
[0044] Comparative Example 2
[0045] BMI-PPG400 disclosed in CN117844435A was used as comparative compound 2.
[0046] Comparison of thermal stability
[0047] The heat resistance of BMI-PPG400, BMI-PPG1000 and BMI-R45V was compared by TGA thermogravimetric analysis (the test equipment was TGA( / DSC3+) thermogravimetric analyzer from Mettler Toledo, Switzerland). 25℃~500℃ Heating rate: 10℃ / min, see Figure 1 .
[0048] It can be seen from thermogravimetric analysis that BMI-R45V (the present invention) has better thermal stability than BMI-PPG1000, with 87% of its mass remaining at 406°C, while the latter loses 13% of its mass due to thermal decomposition at 330°C.
[0049] Application Example 1 and Comparative Application Examples 1-2
[0050] The performance was evaluated by preparing a conductive adhesive, and the preparation method of the conductive adhesive was as follows (Comparative Application Example 1):
[0051] Weigh 15 parts of BMI-PPG1000, 30 parts of liquid polybutadiene 131MA8 grafted with maleic anhydride groups, 33 parts of isobornyl acrylate, 22 parts of difunctional acrylate monomer 238NS, 1 part of peroxide CHPO, and 1 part of silane coupling agent KH-570, add them into a mixing kettle, mix at 800 rpm for 15 min, then add 300 parts of silver powder, disperse at 800 rpm for 15 min, and then vacuum degas for 10 min, with a vacuum degree of <-0.095 MPa; discharge at normal pressure to obtain a conductive adhesive.
[0052] The only difference between Application Example 1 and Comparative Application Example 1 is that the compound BMI-PPG1000 in Comparative Application Example 1 is replaced by an equal amount of BMI-R45V, and the preparation method is the same as that of Comparative Application Example 1.
[0053] The only difference between Comparative Application Example 2 and Comparative Application Example 1 is that the compound BMI-PPG1000 in Comparative Application Example 1 is replaced by an equal amount of BMI-PPG400, and the preparation method is the same as that of Comparative Application Example 1.
[0054] The sources of raw materials are shown in Table 1 below.
[0055] Table 1
[0056]
[0057] (1) Volume resistivity test:
[0058] Refer to the four-probe method of the industry standard "HG / T 5912-2021 Conductive Adhesives",
[0059] Preparation of conductive film: On a glass substrate, a conductive film with a thickness of ~25 μm, a width of 9 mm, and a length of 50 mm was prepared by a controlled thickness tape scraping method; Curing conditions: The test piece was placed in an oven and heated from 25 to 40 °C at a rate of 5 °C / min. o C to 175℃, then 175℃×60 min; Test equipment: TH2516 DC resistance tester from Changzhou Tonghui Electronics Co., Ltd. Test equipment: ZC36 high insulation resistance measuring instrument (Shanghai Precision Instrument Co., Ltd.).
[0060] (2) Chip thrust:
[0061] The test method refers to "HG / T 5912-2021 Conductive Adhesives".
[0062] The silicon wafer size is: 2 mm × 2 mm (thickness 500um); the substrate is a silver-plated copper sheet;
[0063] Curing conditions: The test piece was placed in an oven and heated from 25o The temperature was raised from 175°C to 175°C, and then kept at 175°C for 60 min. The testing equipment was a DAGE-4000P multifunctional push-pull testing machine (Nordson DAGE Precision Industries LTD, USA) with a temperature-controlled heating table. The shear strength was the thrust force (in kgF, kilogram-force). Ten test data were taken from the test samples corresponding to each type of glue, and the arithmetic mean of the results was taken.
[0064] When measuring high-temperature thrust, set the temperature on the temperature-controlled heating platform, wait for the target temperature to be reached and stabilize for 5 minutes before starting to measure the thrust.
[0065] (3) Residual glue rate on broken ring surface:
[0066] Destruction surface evaluation: After the chip thrust test is completed, the substrate is placed on the microscope stage, and the residual glue on the substrate after the thrust damage is observed through an optical microscope. The residual glue area ratio (percentage relative to the chip area) is evaluated for assessment. The scoring system uses a 10-point system, 100% residual glue corresponds to 10; 90% residual glue corresponds to 9, and so on. 10% residual glue corresponds to 1; 0% residual glue corresponds to 0; the arithmetic average of 10 samples is taken. Test equipment: Shanghai Optical Instrument Factory 6XM-PC metallographic microscope. The higher the residual glue rate, the better the bonding performance.
[0067] The test results are shown in Table 2.
[0068] Table 2
[0069]
[0070] From the data in Table 2, it can be seen that compared with comparative application examples 1 and 2, when the BMI resin content is equal, the volume resistivity of the conductive adhesive prepared in application example 1 is lower after curing (better conductivity), the chip thrust at room temperature and high temperature is greatly improved, and the residual adhesive rate on the residual adhesive surface after destruction is also very high, indicating good bonding performance with the silver-plated substrate. The performance improvement may be due to the fact that the main chain molecules of the bismaleimide resin contain more unsaturated double bonds, which increases the crosslinking density during curing.
[0071] The applicant declares that the present invention illustrates the bismaleimide resin and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bismaleimide resin, characterized in that The bismaleimide resin has a structure as shown in Formula 1: ; Formula 1 Wherein R1 is selected from C1-C5 alkylene, n is an integer of 20-40, 0<a<1, 0<b<1, 0<c<1, and a+b+c=1.
2. The bismaleimide resin according to claim 1, characterized in that R1 is selected from -CH2-, -CH2-CH2- or -CH2-CH2-CH2-CH2-CH2-CH2-.
3. The bismaleimide resin according to claim 1, characterized in that The bismaleimide resin is selected from any one of the following resins: ; 。 4. The method for preparing the bismaleimide resin according to claim 1, characterized in that: The preparation method comprises the following steps: The compound represented by formula A reacts with the compound represented by formula B to obtain the bismaleimide resin represented by formula 1. The reaction formula is as follows: ; Wherein R1 is selected from C1-C5 alkylene, n is an integer of 20-40, 0<a<1, 0<b<1, 0<c<1, and a+b+c=1.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the compound represented by formula A to the compound represented by formula B is 3:1-6:
1.
6. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a dehydrating agent; The molar ratio of the compound represented by formula A to the dehydrating agent is 1:1-1:2; The dehydrating agent is selected from at least one of N,N'-dicyclohexylcarbodiimide, diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
7. The preparation method according to claim 4, characterized in that: The reaction is carried out in the presence of a catalyst; The catalyst is selected from at least one of 4-dimethylaminopyridine, 4-pyrrolidinopyridine, hydroxybenzotriazole or diphenylamine trifluoromethanesulfonate.
8. The preparation method according to claim 7, characterized in that: The molar ratio of the catalyst to the compound represented by formula B is 1:10-1:
15.
9. The preparation method according to claim 4, characterized in that: The reaction is carried out at room temperature and the reaction time is 12-24 hours.
10. Use of the bismaleimide resin according to any one of claims 1 to 3 in the preparation of thermosetting materials.
Citation Information
Patent Citations
Cyanate ester composition containing BMI resin and application
CN117844435A
Conductive silver adhesive and preparation method and application thereof
CN106433509A
Debondable adhesives and the high temperature use thereof
CN108699411A